KEPUTUSAN ADOPSI INOVASI PERTANIAN SAYUR ORGANIK - Butarbutar, Kristin Noviani; Levis, Leta Rafael; Chamdra, Santhy (Buletin Ilmiah Impas, 2024)
The decline in the quality of agricultural land due to residues of synthetic chemical inputs is a serious problem being faced in agricultural development in Indonesia. Starting from these problems an important issue of sustainable agricultural development is organic farming. This research has been carried out on CV. GS Organic in 2023, with the aim of a) describing the process of adopting organic farming innovations at CV. GS Organic, b) describes the internal factors and external factors that influence the adoption of organic farming innovations in CV. GS Organic, c) describes the type of organic farming decision making in CV. GS Organic. This type of research is qualitative with a case study approach. Data collection methods are by observation, in-depth interviews and documentation. The data analysis method uses the interactive Miles and Huberman model. The results showed that the factors that determine the adoption of innovation in CV. Organic GS is the initiative of the farmers themselves, as well as the factors that influence farmers' decision making, namely internal factors and external factors. Internal Factors: a) Cosmopolitan Level, b) Motivation. External Factors: a) Reference Group, b) Sources of Information, c) Characteristics of Innovation. Farmers' perceptions of the characteristics of innovation that determine innovation adoption are relative advantages from an economic standpoint, advantages from a social prestige perspective, relative advantages from a convenience standpoint, conformity with espoused values, conformity with prevailing norms, conformity with farmer's needs, trialability (Triability). in a small area, ability is observed from technical advantages, ability is observed from the point of view of economic advantage. The type of decision made on the CV. Organic GS in making decisions, namely optional decisions.